2019
DOI: 10.3389/fimmu.2019.00418
|View full text |Cite
|
Sign up to set email alerts
|

GRA24-Based DNA Vaccine Prolongs Survival in Mice Challenged With a Virulent Toxoplasma gondii Strain

Abstract: Toxoplasma gondii causes infections in a wide range of intermediate hosts and remains a threatening disease worldwide because of the lack of effective drugs and vaccines. Dense granule protein 24 (GRA24) is a novel essential virulence factor that is transferred into the nucleus of host cells from the parasitophorous vacuole to regulate gene expression. In the present study, bioinformatic analysis showed that GRA24 had a high score for B-cell and T-cell epitopes compared with surface antigen 1 (SAG1), which has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 56 publications
5
38
1
Order By: Relevance
“…Our results showed that among the three recombinant proteins, roVP3 induced the highest levels of specific IgG in the serum. IL-2 and INF-γ are mainly secreted by Th1 cells, which promote cellular immune responses and IL-4 and IL-10 are mainly secreted by Th2 cells, which promote humoral immune responses (Wang et al, 2017;Zheng et al, 2019). Comparing SI values and and cytokines, we speculate that roVP2 has a strong effect on cellular immune responses and that roVP3 can induce a strong humoral immune response in the mice, although all the three recombinant proteins could stimulate cellular and humoral immune responses.…”
Section: Discussionmentioning
confidence: 88%
“…Our results showed that among the three recombinant proteins, roVP3 induced the highest levels of specific IgG in the serum. IL-2 and INF-γ are mainly secreted by Th1 cells, which promote cellular immune responses and IL-4 and IL-10 are mainly secreted by Th2 cells, which promote humoral immune responses (Wang et al, 2017;Zheng et al, 2019). Comparing SI values and and cytokines, we speculate that roVP2 has a strong effect on cellular immune responses and that roVP3 can induce a strong humoral immune response in the mice, although all the three recombinant proteins could stimulate cellular and humoral immune responses.…”
Section: Discussionmentioning
confidence: 88%
“…This nding was similar to the results from BALB/c mice immunized with T. gondii exosomes that produced high levels of IFN-γ and IL-12 but no signi cant differences in the levels of IL-4 and IL-10 after T. gondii infection [30]. Pregnant mice immunized with T. gondii GRA17 or GRA24 produced high levels of IL-10, which could modulate the pathological damage in foetal mice induced by a large amount of the Th1 cytokine IFN-γ induced by T. gondii challenge [31,39]. BALB/c mouse vaccination with the recombinant protein rNcSRS2 of N. caninum promoted the upregulation of IL-10 expression [40].…”
Section: Discussionmentioning
confidence: 99%
“…When N. caninum invasion occurs, the parasite can be captured and processed by antigen-presenting cells and then presented to T lymphocytes, which further builds adaptive immunity. When N. caninum invades subsequently, speci c anti-N. caninum IgG antibodies adhere to the surfaces of the parasites and limit their spread by preventing attachment to host cell receptors, resulting in their elimination by macrophages [31,32]. Humoural immunity is important in eliminating pathogens, strengthening the elimination of invasive microbes, and building immunological memory to protect against reinfection.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, an increase in IL-10 and IL-4 levels was also observed in mice, which received a low dose of lumefantrine ( P ≤ 0.01). IL-10 has a central role in limiting inflammation and inhibiting CD4+ T cell-mediated severe immunopathology (Dupont et al ., 2012), and IL-4 functions to enhance IFN- γ production in the late stage of infection (Zheng et al ., 2019 b ).…”
Section: Discussionmentioning
confidence: 99%